The Think Pair Share Learning Model's Active Learning Process in Basic Electrical Subjects at SMKN 1 Lhoknga, Aceh - Azmi, Faisal; Fathiah, Fathiah; Fachri, Muhammad Rizal (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
Vocational high school curriculum aimed to prepare pupils for careers in specific industries. Student learning results are significantly impacted by the vocational school learning process. Students' comprehension at SMKN 1 Lhoknga is still deficient since the learning model used is not as effective in maximizing the growth of students' understanding. Applying the Think Pair Share learning paradigm, which is in line with the learner-centered curriculum, is one option to solve this issue. This study employs a quantitative methodology and involved 27 pupils in class X TITL SMKN 1 Lhoknga. Questionnaires and observation sheets are the tools employed. The findings demonstrated that, according to the Think Pair Share learning model, students' average level of activity was 79, with a trend of 79 > 73.3, placing them in the very high category. The percentage of students who responded is 77.04%. it can be concluded that the utilization of the Think Pair Share approach can raise students' engagement with basic electrical materials, according to the study's findings.